175k views
1 vote
⚠️Please reply ASAP, I would like to check my answer with someone, thank you

Answering just for points will be reported

⚠️Please reply ASAP, I would like to check my answer with someone, thank you Answering-example-1

1 Answer

3 votes

Answer:

(2, 3 ) and (- 2, 11 )

Explanation:

f(x) = x² - 2x + 3 → (1)

f(x) = - 2x + 7 → (2)

Substitute f(x) = x² - 2x + 3 into (2)

x² - 2x + 3 = - 2x + 7 ( add 2x to both sides )

x² + 3 = 7 ( subtract 3 from both sides )

x² = 4 ( take the square root of both sides )

x = ±
√(4) = ± 2

Substitute these values into (2) for corresponding values of y

x = 2 : y = - 2(2) + 7 = - 4 + 7 = 3 ⇒ (2, 3 )

x = - 2 : y = - 2(- 2) + 7 = 4 + 7 = 11 ⇒ (- 2, 11 )

User Sigod
by
5.0k points